(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This study explores the socioeconomic determinants of traditional healthcare utilization in Calabar Metropolis, Cross River State, Nigeria. The research investigates the relationship between occupation, income level, educational level, and the use of traditional healthcare services. A survey design was employed, with 402 respondents selected through multistage sampling from six randomly chosen streets across the Calabar Municipality and Calabar South. The study’s hypotheses were tested to determine the significance of the relationship between these socioeconomic factors and healthcare utilization. Findings reveal that occupation does not significantly influence traditional healthcare utilization, while both income level and educational level show a perfect positive correlation with usage. Based on these results, the study recommends enhanced social investment programs to address income inequality and improve healthcare access. It also advocates for increased public awareness through collaborative campaigns by the government, NGOs, and media to educate the public on the benefits of traditional healthcare services in in Calabar Metropolis, Cross River State, Nigeria.